Toward more mechanistic representations of biogeochemical processes in river networks: Implementation and demonstration of a multiscale model. (November 2021) - Jan, Ahmad; Coon, Ethan T.; Painter, Scott L.
Abstract: A recently introduced multiscale model for representing the effects of small-scale hyporheic-zone biogeochemical processes is extended from the reach scale to river network scales. The model uses advection-dispersion-reaction equations for the channel network and one-dimensional advection-reaction subgrid models for the hyporheic zone. We summarize implementation in the integrated surface/subsurface hydrology modeling system Amanzi-ATS. The extension uses topologically defined meshes to represent stream/river networks and associates a hyporheic subgrid model with each channel grid cell. Biogeochemical reaction modeling capability residing in community software is accessed through an application programming interface. The implementation is verified against independent numerical solutions on a single reach. Mesh convergence studies show that commonly used semi-distributed representations can introduce significant spatial discretization error. Denitrification of farm runoff in a subbasin of the Portage River Basin in Ohio, USA is used to demonstrate the general-purpose reactive transport capability. Highlights: A new model for reactive transport in river networks is implemented in Amanzi-ATS. Hyporheic-zone reactions are explicitly represented in network-scale models. Simulations of denitrification in stream networks show complex spatial variability. The model has smaller discretization error compared with semi-distributed models.